Contrasting effects of the cyanobacterium Microcystis aeruginosa on the growth and physiology of two green algae, Oocystis marsonii and Scenedesmus obliquus, revealed by flow cytometry. (29th May 2013) - Dunker, Susanne; Jakob, Torsten; Wilhelm, Christian
Summary Aquatic photosynthetic productivity is influenced by resource availability, resource use efficiency and interspecific interactions. In hypertrophic environments, interspecific interference is known to influence species succession. The effect of interference by phytoplankton on biomass production is very poorly understood. One hypothesis is that the development of cyanobacterial blooms is triggered by the excretion of allelopathic substances that inhibit the growth of other phytoplankton species. In this study, we analysed how the co‐cultivation of the cyanobacterium Microcystis aeruginosa with two green algae (Oocystis marsonii and Scenedesmus obliquus) influences the resource use efficiency of each partner under nutrient‐replete conditions. Using single‐cell technologies, it was possible to quantify the efficiency of light use and the biomass gain for all three species under hypertrophic (non‐limiting nutrient) conditions. The presence of M. aeruginosa resulted in growth inhibition, reduced metabolic activity and an increased quantum requirement for biomass assimilation in O. marsonii, whereas no changes were observed in S. obliquus. M. aeruginosa, on the other hand, showed an increased cell size in mixed cultures with O. marsonii. However, with respect to biomass production, M. aeruginosa did not profit from the growth inhibition of O. marsonii in the experimental period of 8 days. By contrast, the co‐cultivation of M. aeruginosa with S. obliquus did not affect the physiological activity of either species. This study highlights the potential of flow cytometry to determine species‐specific basic growth parameters, light‐use efficiency and biomass gain during co‐cultivation of different algal strains. It is further demonstrated that sorted cells can be used to analyse their macromolecular composition. The results of this study reveal very different species‐specific patterns of growth kinetics and light‐use‐efficiency of green algae in co‐cultivation experiments with a cyanobacterium.